Domain Cognizance and Essential Skills required for Employability of Electronics and Telecommunication Engineering Graduates in Maharashtra (India) - An Alumnus Perspective - Patil, Rupesh J.; Charak, Kuldip S.; Charak, Kuldip S. (International Journal of Psychosocial Rehabilitation, 2020)
Engineering colleges in Maharashtra has produced thousands of Electronics and Telecommunication Engineering graduates. Employability of Engineering Graduates has become a biggest concern for the Institutions, Industries and related government agencies. Year by year, the Intake reduction of engineering institutesis becoming the problem of concern for the faculties, Private college owners and ultimately all direct and indirect stakeholders related to the education system.This research paper is the portion of the research work in understanding and analyzing the employable parameters of engineering graduates from Maharashtra (India).The research work is based on the feedback of Alumni of these colleges from E&TC stream. Feedback on four variables is considered for assessment of Skills. The data used in the research is obtained from alumni who graduated between AY 2000 to AY 2018.Descriptive and inferential statistical analyses is used to analyze the data.